Treatment of Aggressive Pituitary Adenomas: A Case-Based Narrative Review - Cooper, Odelia; Bonert, Vivien; Liu, Ning-Ai; Mamelak, Adam N. (Frontiers in Endocrinology, 2021)
Management of aggressive pituitary adenomas is challenging due to a paucity of rigorous evidence supporting available treatment approaches. Recent guidelines emphasize the need to maximize standard therapies as well as the use of temozolomide and radiation therapy to treat disease recurrence. However, often these adenomas continue to progress over time, necessitating the use of additional targeted therapies which also impact quality of life and long-term outcomes. In this review, we present 9 cases of aggressive pituitary adenomas to illustrate the importance of a multidisciplinary, individualized approach. The timing and rationale for surgery, radiation therapy, temozolomide, somatostatin receptor ligands, and EGFR, VEGF, and mTOR inhibitors in each case are discussed within the context of evidence-based guidelines and clarify strategies for implementing an individualized approach in the management of these difficult-to-treat-adenomas.